Congenital facial nerve palsy: Single center study - Baelen, Hermine; Esschendal, Anne-Marie; De Brucker, Yannick; Foulon, Ina; Topsakal, Vedat; Gordts, Frans (Frontiers in Pediatrics, 2023)
Objectives: This study will list the most common comorbidities of inborn facial nerve palsy and how to detect and treat them. Inborn facial nerve palsy is a very rare entity but in UZ Brussels hospital there was a follow-up of 16 children in the last 30 years. Methods: Literature review has been done, combined with thorough research of our own series of 16 children with inborn facial nerve palsy. Results: Inborn facial nerve palsy can be part of a known syndrome, most commonly Mobius syndrome, but can also appear solely. It appears often bilateral and with a severe gradation. In our series, hearing loss is frequently seen in association with inborn facial nerve palsy. Other abnormalities are dysfunction of the abducens nerve, ophthalmological problems, retro- or micrognathism and abnormalities of limbs or heart. The majority of the children in our series underwent radiological imaging (CT and/or MRI): the facial nerve but also the vestibulocochlear nerve and middle and inner ear can be evaluated. Conclusion: A multidisciplinary approach of inborn facial nerve palsy is recommended as it can affect various bodily functions. Radiological imaging needs to be done to acquire additional information that can be useful for diagnostic and therapeutic purposes. Although inborn facial nerve palsy may not be treatable itself, its comorbidities can be treated and improve the quality of life of the affected child.